Mathematical modeling of cyclic treatments of chronic myeloid leukemia - Natalia L. Komarova (Mathematical Biosciences and Engineering)
Cyclic treatmentstrategies in Chronic Myeloid Leukemia (CML) are characterized byalternating applications of two (or more) different drugs, given oneat a time. One of the main causes for treatment failure in CML is thegeneration of drug resistance by mutations of cancerous cells. We usemathematical methods to develop general guidelines on optimal cyclictreatment scheduling, with the aim of minimizing the resistancegeneration. We define a condition on the drugs' potencies which allowsfor a relatively successful application of cyclic therapies. We findthat the best strategy is to start with the stronger drug, but uselonger cycle durations for the weaker drug. We further investigate thesituation where a degree of cross-resistance is present, such thatcertain mutations cause cells to become resistant to both drugssimultaneously.